THE EFFECT OF THE EXCHANGE RATE ON THE INDONESIAN TRADE BALANACE IN THE MANAGED FLOATING EXCHANGE RATE SYSTEM AND FLEXIBLE EXCHANGE RATE SYSTEM (PERIOD 1980 to 2020) - Amaliawiati, Lia; Nursjanti, Farida; Puspitasari, Devy Mawarnie; Roespinoedji, Djoko (CENTRAL ASIA AND THE CAUCASUS, 2022)
The aim of this research is to look at the impact of the exchange rate on Indonesia's trade balance in the short term and long term during the controlled/managed floating exchange rate system and the floating/flexible exchange rate system, as well as to see if there are any differences between the controlled/managed floating exchange rate system and the floating/flexible exchange rate system. This study uses times series data for the period 1980 - 2020 by including dummy variables. The first stage is to test the data stationarity with the unit root test and the results are mostly stationary data at the first difference. Furthermore, Based on the results of the cointegration test, it turns out that there has been cointegration between variables so that to see the balance of the regression model both in the short and long term, the error correction model (ECM) is used, and the results show that in the short term using a floating exchange rate system the exchange rate affects the foreign trade balance, while with a controlled floating exchange rate system the exchange rate affects the foreign trade balance. Meanwhile, in the long term using a floating exchange rate system, the exchange rate affects the foreign trade balance, while in a controlled floating exchange rate system the exchange rate does not affect the foreign trade balance.Other results show that there is a difference in the average trade balance variable during the floating system with managed/controlled floating only for the export price index and economic growth.